In the mind's eye: Enhancing human performance - Druckman, D.; Bjork, R. A. (1992)
Front Matter i-iv Contents v-vi Preface vii-xii Part I Overview 1-2 1 Background 3-11 2 Findings and Conclusions 12-20 Part II Training 21-22 3 Optimizing Long-Term Retention and Transfer 23-56 4 Modeling Expertise 57-79 5 Developing Careers 80-104 Part III Altering Mental States 105-106 6 Subliminal Self-Help 107-119 7 Meditation 120-133 8 Managing Pain 134-147 9 Hiding and Detecting Deception 148-170 10 A Broader Concept of Deception 171-190 Part IV Performing 191-192 11 Optimizing Individual Performance 193-246 12 Enhancing Team Performance 247-270 Appendix A: Committee Activities 273-275 Appendix B: Biographical Sketches 276-282 Index 283-291